Reforming Teacher Education - SHARMA, SANTOSH (THE PRIMARY TEACHER, 2014)
The need to reform teacher education in India has been expressed in various commissions and committees on ‘Teacher Education’ but very few concrete steps have been taken during the past fifty years. Let us examine what various commissions and committees say about teacher education reforms. The Kothari Commission (1964-66) noted that there is a need to bring teacher education into the mainstream of the academic life of universities on the one hand and of school life and educational development on the other. The Commission recommended the introduction of “integrated courses of general and professional education in universities with greater scope for self-study and discussion and a comprehensive programme of internship.” The Chattopadhyaye Committee (1983-85) reiterated the concurrent model of teacher education that is, general and professional education to be pursued concurrently. The Commission recommended that the length of these concurrent courses following the completion of Class XII be five years. Both the Kothari Commission and Chattopadhyaye Committee recommend concurrent programmes for teacher education and the placing of these programmes in universities.